Проблеми та перспективи грінвошінгу за глобалізаційних умов та розвитку циркулярної економіки - Макарова, Ю. С.; Завербний, А. С.; Makarova, Yu. S.; Zaverbnyj, A. S. (Видавництво Львівської політехніки, 2005)
Розглянуто трактування поняття «greenwashing» та визначено походження цього поняття як наукового терміну. Визначено ступінь впливу greenwashing на маркетинг, бізнес та репутацію компанії. Для цього було приведено приклади використання всесвітньовідомими брендами greenwashing та наслідки для них на ринку. Було визначено різницю між зеленим маркетингом та greenwashing, а також наведено приклади компаній, які використовують зелений маркетинг, зазначено, наскільки великим є позитивний вплив на їхню репутацію після застосування правдивих тверджень замість оманливих. У висновку наведено методи уникнення використання greenwashing маркетологами, а також зазначені способи для споживачів, як не стати жертвою оманливої реклами.

An urgent problem that arises in the practices of green marketing is the growth of greenwashing; companies that provide inappropriate, exaggerated or false information about product quality. This article provides information on the impact of greenwashing on consumers. The interpretation of the concept of «greenwashing» is considered and the origin of this concept as a scientific term is determined. The Green Code of Claims has been studied, which contains the principles on the basis of which companies have the right to announce the environmental friendliness of their products and conduct green advertising. The eight main strategies of modern companies that use greenwashing and the main consequences for consumers after identifying such strategies are analyzed. This leads to misleading information for both investors and consumers. The degree of influence of greenwashing on the marketing, business and reputation of the company is determined. For this purpose, examples of the use of world-famous greenwashing brands and their implications for the market were given. Companies and brands are crossing the line between greenwashing and green marketing. The distinction between green marketing and greenwashing was identified, as well as examples of companies that use green marketing, and the impact of a positive impact on their reputation after using truthful statements instead of false ones. In conclusion, there are methods to avoid the use of greenwashing by marketers, as well as these ways for consumers not to fall victim to misleading advertising. Recommendations were also given to businesses on how to avoid greenwashing and build a positive reputation for their company, which will eventually increase the organization's profits by targeting the market for green products. If the company is working to achieve sustainability goals, it is better to share the true history of the brand with your audience, but you do not need to destroy the reputation of the brand just because the company wants to catch the trend.
Problems and prospects of greenwashing under globalization conditions and development of circular economy
Keywords: greenwashing; зелений маркетинг; стійкість підприємства; екологічність; претензії споживачів; реклама; Управлінням із стандартів реклами (ASA); greenwashing; green marketing; stability of the enterprise; environmental friendliness; consumer claims; advertising; Office of Advertising Standards (ASA); 504.054; 574; 631.1; 657; 658.8